China and the World Bank - Gehring, Kai,Kaplan, Lennart,Wong, Melvin Heen Lung (CESifo, Center for Economic Studies & Ifo Institute, 2019)
China's development model challenges the approaches of traditional Western donors like the World Bank. We argue that both aim at stability, but differ in the norms propagated to achieve that. Using fixed effects and IV estimations, we analyze a broad range of subnational stability measures in Africa. Aid by both the WB and China does not increase outright conflict nor any type of citizen protest, on average. Both even reduce outright conflict by governments against civilians. Still, Chinese aid is associated with more government repression and an increased acceptance of authoritarian norms, while WB projects strengthen democratic values.
10419/207247
Keywords: Graue Literatur; Entwicklungsmodell; Vergleich; Entwicklungshilfe; Auswirkung; Innenpolitik; Politischer Konflikt; Korrelation; Statistische Analyse; Empirie; development models; development aid; stability; conflict; repression; World Bank; China; Africa; geolocation